Optimizing Rolling Strategies for API 5L X80 Steel Heavy Plates Produced by Thermomechanical Processing in a Reversible Single-Stand Mill - de Oliveira Abreu, Luiz Gustavo; de Faria, Geraldo Lúcio; de Faria, Ricardo José; Matsubara, Daniel Bojikian; Porcaro, Rodrigo Rangel (Metals (Basel ), 2024)
This study focuses on advancing the production of predominantly bainitic heavy plates to meet the API 5L X80 standard. The investigation involves a thorough evaluation of the influence of rolling parameters and austenite conditioning on both microstructural characteristics and mechanical properties. Accurate specifications for chemical composition, processing temperatures, and mean deformations were established using mathematical models and bibliographical references. Four rolling conditions were performed in a reversible single-stand mill, allowing for comprehensive comparison and critical analysis. Microstructural and mechanical characterizations were performed utilizing several techniques, including optical microscopy (OM), scanning electron microscopy (SEM), tensile tests, Charpy impact tests, and hardness tests to ensure adherence to API 5L standards. Additionally, the SEM-EBSD (electron backscattered diffraction) technique was employed for a complementary analysis. The EBSD analysis included crystallographic misorientation maps, mean kernel misorientation parameters (ϑ), low- and high-angle grains boundaries, mean equivalent diameter, and evaluation of the contribution of different strengthening mechanisms to yield strength. Results underscored the significant influence of austenite conditioning on both microstructure and mechanical properties. Considering the specificities of a reversible single-stand mill, it was concluded that, unlike the classic approach for ferritic or ferritic–pearlitic HSLA (high-strength low-alloy steel), when a product with a predominantly bainitic microstructure is required, the accumulated deformation in the austenite during the finishing rolling stage, as well as its temperature, must be meticulously controlled. It was shown that the greater the deformation and the lower the temperature, the more favorable the scenario for the undesired polygonal ferrite formation, which will deteriorate the material’s performance. Furthermore, an optimized production route was identified and adapted to the specificities of the employed rolling mill. The presented data have great importance for researchers, manufacturers, and users of API 5L X80 heavy plates.